Manifestações bucais da Leucemia Linfoblástica em pacientes infantojuvenis - estudo clínico prospectivo em Centro de Referência Hematológico do Amazonas - de Mello e Pias, Melina Cuenca (2020)
Lymphoblastic Leukemia (LL) and its treatment are capable of inducing buccal manifestations. OBJECTIVE: To clinically and prospectively evaluate the buccal mucosa of infant juvenile patients diagnosed with lymphoblastic leukemia (LL). METHODS: Within 12 months, from September/18 until August/19, 36 patients diagnosed with B or T-cell precursor LL, with ages ranging from 1 to 14 years old, who were treated at Amazon Hematology and Hemotherapy Foundation - HEMOAM under GBTLI-LLA 2009 or ALL IC-BFM 2009 protocols were consecutively enrolled. The buccal mucosa was clinically evaluated respectively on the first (D0/D1) and fifteenth (D15) days of prophase/induction phase of chemotherapy (QT). RESULTS: Out of the 36 patients found within the proposed period, 25 had their buccal mucosa evaluated. Eleven of them (44% n=11) showed buccal manifestations, especially in D0/D1. The manifestations and their respective frequency were petechiae (31,6%; n=6), dry lips (26,3%, n=5) and buccal mucositis (15,8%, n=3). Non-keratinized mucosa was the preferred site (84,2%, n=16). Of the 25 patients, 64% (n=16) were male with a median age of 6,9 years old. The majority had B-cell precursor LL (96%; n=24). CONCLUSIONS: Buccal manifestations have a low incidence in infant juvenile patients with LL, just as the majority of the patients 56% (n=14) showed healthy mucosa. This fact could be due to our small sample or the low toxicity from the protocols and dental team present at the Institution